Survey On Career Interest of Sharia Economic Law Students In The Final Semester - Nur Rizqi Febriandika; Fajriyanti Fatimah; Putri Wirayanti (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to map the career interests of Islamic economic law students after graduating from college. Sharia economic law is a unique study program because it combines several major scientific competencies, namely law, economics, and sharia science. The type of research is descriptive qualitative research by distributing questionnaires. Data collection methods include filling out questionnaires, interviews, observations, and documentation. This study indicates that 74% of the samples taken choose to work directly rather than continue their master's studies (S2). The biggest factor influencing career choice is own desire (74%). The first priority that is most in-demand are Islamic financial institutions with 23%, the selected jobs that are the second priority that is most in demand are in non-bank companies 38%. Meanwhile, students who want to continue their studies after graduation tend to choose masters with the same major, namely the master of sharia economic law (16%). The implementation of a law degree for graduates of Islamic Economic Law has a very large advantage for graduates of Islamic Economic Law, but many students choose to work in the field of economics even though the degree obtained is a law degree because there is still a lack of understanding of law compared to law graduates from the law faculty itself. Keywords: Career, Sharia Economic Law, Students